Investigating Random Laser From Aluminium-doped Zinc Oxide Nanorods - Ali, Abdullah Taha (2022)
In this research, random lasing (RL) properties are investigated from Aluminium-doped Zinc oxide (AZO) nanorods (NRs) prepared by chemical bath deposition (CBD) method, then capped with silicon dioxide (SiO2) layer by radio frequency sputtering technique. The integration of the two approaches aims to improve ultraviolet RL emission from AZO NRs whilst enabling lasing tunability by adjusting doping parameters. Therefore, this work is divided into three parts. The first part is to determine the optimal growth conditions for AZO NRs. The second part is to identify RL emission properties from AZO NRs. The third part focuses on investigating the effect of having SiO2 capping layer on ZnO NRs and AZO NRs by varying SiO2 thicknesses. The structural, morphological, optical and electrical properties of the samples were also investigated for clarity. Increasing Al concentration during the CBD process led to a decrease in the growth rate and showed an increase in the size of NRs. This becomes a problem in identifying the RL properties that is due to doping since there is significant changes in morphology or structure. A different attempt in increasing the Al doping percentage was done by varying the CBD temperature at a fixed concentration of 5mM, this concentration, which was determined to be the maximum concentration that preserves the morphology of AZO NRs, demonstrated to solve this problem. The sample with the highest doping (1.72 at.%) exhibited the lowest lasing threshold of 0.192 mW with spectral width less than 0.08 nm.